Genome Analysis and Physiological Characterization of Four Streptococcus thermophilus Strains Isolated From Chinese Traditional Fermented Milk - Hu, Tong; Cui, Yanhua; Zhang, Yishuang; Qu, Xiaojun; Zhao, Chunyu (Frontiers in Microbiology, 2020)
Streptococcus thermophilus plays important roles in the dairy industry, and is widely used as a dairy starter in the production of fermented dairy products. The genomes of S. thermophilus strains CS5, CS9, CS18 and CS20 from fermented milk in China were sequenced and used as for the biodiversity analysis. In the present study, the phylogenetic analysis of all 34 S. thermophilus genomes publicly available including these four strains reveals that the phylogenetic reconstruction does not match geographic distribution as strains isolated from the same continent are not even clustered on the nearby branches. The core and variable genes were also identified, which vary among strains from 0 to 202. CS9 strain contained 127 unique genes from a variety of distantly related species. It was speculated that CS9 had undergone horizontal gene transfer (HGT) during the long evolutionary process. The safety evaluation of these four strains indicated that none of them contain antibiotic resistance genes and that they are all sensitive to multiple antibiotics. In addition, the strains do not contain any pathogenic virulence factors or plasmids and thus can be considered safe. Furthermore, these strains were investigated in terms of their technological properties including milk acidification, exopolysaccharide (EPS) and γ-aminobutyric acid (GABA) production, and in vitro survival capacity in gastrointestinal tract (GIT). CS9 possesses a special eps gene cluster containing significant traces of HGT, while the eps gene clusters of CS5, CS18 and CS20 are almost same. The monosaccharide compositional analysis indicated that crude EPS-CS5, EPS-CS9, EPS-CS18, and EPS-CS20 contain similar monosaccharide compositions with different ratios. Furthermore, CS9 was one of a few GABA-producing strains that could ferment glutamate to produce GABA, which is beneficial for improving the acid tolerance of strain. CS18 has the most potential for the production of fermented food among these four strains because of its fast growth rate, rapid acidifying capacity, and stronger acid and bile salt resistance capacity. This study focused on the genome analysis of the four new S. thermophilus strains to investigate the diversity of strains, and provides a reference for selecting excellent strains by use of the genome data.